Self-talk functions: portrayal of an elite power lifter - Cutton, D. M.; Hearon, C. M. (Perceptual and Motor Skills, 2014)
The study presents the results of a case study with a repeated data collection design: a recent and former world champion power lifter provided weekly e-mails, during approximately 6 mo. of training and competition, with a description of his `self-determined self-talk.` The instruction used for self-talk (ST) mentioned its associations with emotions, staying focused, maintaining motivation, and improving exercise skills. The obtained e-mails were coded using categories indicating functions of `self-determined self-talk` mainly based on previous literature. The frequency of the functions during training and competition were compared and discussed following the qualitative research tradition.